2023
DOI: 10.1073/pnas.2219179120
|View full text |Cite
|
Sign up to set email alerts
|

Confined water–encapsulated activated carbon for capturing short-chain perfluoroalkyl and polyfluoroalkyl substances from drinking water

Abstract: The global ecological crisis of perfluoroalkyl and polyfluoroalkyl substances (PFASs) in drinking water has gradually shifted from long-chain to short-chain PFASs; however, the widespread established PFAS adsorption technology cannot cope with the impact of such hydrophilic pollutants given the inherent defects of solid–liquid mass transfer. Herein, we describe a reagent-free and low-cost strategy to reduce the energy state of short-chain PFASs in hydrophobic nanopores by employing an in situ constructed confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Positive binding energies were observed with a higher proportion of PFOA molecules forming coordination bonds (Figure S27), whereas negative binding energies were found when more PFOA molecules were physically adsorbed (Figure S28). Remarkably, a lower adsorption energy was observed upon increasing the adsorbed PFOA molecules, indicating a synergistic effect between the coordinated and free PFOA molecules due to their hydrophobicity, which can facilitate the adsorption process . The maximum adsorption capacity was calculated to be 52.58 PFOA molecules per unit cell (Figure S29), corresponding to 3.29 PFOA molecules per ligand, thereby matching the experimental adsorption capacity.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Positive binding energies were observed with a higher proportion of PFOA molecules forming coordination bonds (Figure S27), whereas negative binding energies were found when more PFOA molecules were physically adsorbed (Figure S28). Remarkably, a lower adsorption energy was observed upon increasing the adsorbed PFOA molecules, indicating a synergistic effect between the coordinated and free PFOA molecules due to their hydrophobicity, which can facilitate the adsorption process . The maximum adsorption capacity was calculated to be 52.58 PFOA molecules per unit cell (Figure S29), corresponding to 3.29 PFOA molecules per ligand, thereby matching the experimental adsorption capacity.…”
Section: Resultssupporting
confidence: 63%
“…Remarkably, a lower adsorption energy was observed upon increasing the adsorbed PFOA molecules, indicating a synergistic effect between the coordinated and free PFOA molecules due to their hydrophobicity, which can facilitate the adsorption process. 41 The maximum adsorption capacity was calculated to be 52.58 PFOA molecules per unit cell (Figure S29), corresponding to 3.29 PFOA molecules per ligand, thereby matching the experimental adsorption capacity. Overall, these calculations further highlight the crucial role of the additional open coordination sites and a favorable porous environment in facilitating the adsorption of PFOA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The efficiency of AC decreases significantly for shorter‐chain PFAS (Inyang & Dickenson, 2017; Xiao et al, 2013). Short‐chain PFAS compounds, which have lower potential energy in water, tend to remain dissolved in water rather than binding to adsorbents (Shi et al, 2023). When dealing with drinking water, it was observed that AC's removal efficiency decreases from about 80% for long‐chain PFAS to around 40% for short‐chain compounds, and short‐chain PFAS desorb readily from adsorbents (Park et al, 2020).…”
Section: Introductionmentioning
confidence: 99%